Antiferroelectric to ferroelectric phase switching and dielectric properties of Ba doped lead lanthanum zirconate stannate titanate ceramics. (1st November 2013) - Zhang, N; Feng, Y J; Xu, Y H; Xu, Z
<x xml:space="preserve">Abstract</x> Antiferroelectric to ferroelectric phase transition induced by electric field is accompanied by large strain and significant hysteresis. The effects of barium addition on the electrical and dielectric properties of (Pb0·94−xLa0·04Bax)(Zr, Sn, Ti)O3 antiferroelectric ceramics were investigated, with the intention of reducing phase switching field and hysteresis for actuator applications. The experimental results showed the switching field and electric hysteresis reduced with increasing Ba content, while the magnitude of longitudinal strain was almost unchanged. Further increase in Ba content destabilises the antiferroelectric state when the doping concentration reaches 8 mol.-%. The maximum value of dielectric constant max increased and the temperature Tm that corresponds to the maximal dielectric constant decreased with increasing Ba content. The barium modification causes the phase transition more diffuse.